De Phuket à Lombok : des plages d’Asie du Sud-Est dans la mondialisation touristique - Emmanuel Jaurand (Bulletin de l’Association de Géographes Français, 2021)
As it experiences strong growth in international and domestic tourism, Southeast Asia is a key region for examining contemporary tourism globalization. The coasts are privileged areas for studying social dynamics and territorial restructuring linked to the current tourism dynamics. Through their beaches, Phuket (Thailand), Bali and Lombok (Indonesia), particularly, show the development of multiple territorialities associated with different uses and users. The simultaneous presence of Asian and Western beach users, whose practices differ in part, makes these beaches privileged observatories of the construction of the World as a space for social and cultural interactions.